Chromosome and Plasmids of the Tick-Borne Relapsing Fever Agent Borrelia hermsii - Barbour, Alan G. (Genome Announc, 2016)
The zoonotic pathogen Borrelia hermsii bears its multiple paralogous genes for variable antigens on several linear plasmids. Application of combined long-read and short-read next-generation sequencing provided complete sequences for antigen-encoding plasmids as well as other linear and circular plasmids and the linear chromosome of the genome.